Clopidogrel Monotherapy After 1-Month Dual Antiplatelet Therapy in Percutaneous Coronary Intervention: From the STOPDAPT-2 Total Cohort. (1st August 2022) - Obayashi, Yuki; Watanabe, Hirotoshi; Morimoto, Takeshi; Yamamoto, Ko; Natsuaki, Masahiro; Domei, Takenori; Yamaji, Kyohei; Suwa, Satoru; Isawa, Tsuyoshi; Watanabe, Hiroki; Yoshida, Ruka; Sakamoto, Hiroki; et al.
Abstract : Background: The benefit of clopidogrel monotherapy after 1-month dual antiplatelet therapy (DAPT) compared with 12-month DAPT with aspirin and clopidogrel was demonstrated in the STOPDAPT-2 (Short and Optimal Duration of Dual Antiplatelet Therapy After Everolimus-Eluting Cobalt-Chromium Stent-2), but not in the STOPDAPT-2 acute coronary syndrome (ACS); however, both trials were underpowered based on the actual event rates. Methods: We obtained the prespecified pooled population of 5997 patients as the STOPDAPT-2 total cohort (STOPDAPT-2: N=3009/STOPDAPT-2 ACS: N=2988; ACS: N=4136/chronic coronary syndrome [CCS]: N=1861), comprising 2993 patients assigned to 1-month DAPT followed by clopidogrel monotherapy, and 3004 patients assigned to 12-month DAPT with aspirin and clopidogrel after percutaneous coronary intervention. The primary end point was the composite of cardiovascular (cardiovascular death, myocardial infarction, definite stent thrombosis, or any stroke) or bleeding (Thrombolysis in Myocardial Infarction major/minor) end points at 1 year. Results: One-month DAPT was noninferior to 12-month DAPT for the primary end point (2.84% versus 3.04%; hazard ratio [HR], 0.94 [95% CI, 0.70–1.27]; P noninferiority =0.001; P superiority =0.68). There was no significant risk-difference for the cardiovascular end point between the 1- and 12-month DAPT groups (2.40% versus 1.97%; HR, 1.24 [95% CI, 0.88–1.75]; P noninferiority =0.14; P superiority =0.23). There was a lower risk of the bleeding end point with 1-month DAPT relative to 12-month DAPT (0.50% versus 1.31%; HR, 0.38 [95% CI, 0.21–0.70]; P superiority =0.002). One-month DAPT relative to 12-month DAPT was associated with a lower risk for major bleeding regardless of ACS or CCS (ACS: HR, 0.46 [95% CI, 0.23–0.94]; P =0.03, and CCS: HR, 0.26 [95% CI, 0.09–0.79]; P =0.02; P interaction =0.40), while it was associated with a numerical increase in cardiovascular events in ACS patients, but not in CCS patients, although not statistically significant and without interaction (ACS: HR, 1.50 [95% CI, 0.99–2.27]; P =0.053, and CCS: HR, 0.74 [95% CI, 0.38–1.45]; P =0.39; P interaction =0.08). Conclusions: Clopidogrel monotherapy after 1-month DAPT compared with 12-month DAPT with aspirin and clopidogrel had a benefit in reducing major bleeding events without being associated with increase in cardiovascular events. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT02619760, NCT03462498.